FUNGSI SUPERVISI PENDIDIKAN - Henny Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
The purpose of national education is to educate the life of the nation and to develop a whole human being, that is man who is virtuous with noble character, possesses knowledge and skills, physical and spiritual health, solid and independent personality and sense of community responsibility and nationality. The purpose of educational supervision is to help teachers to better understand / realize the goals of education in schools, and the function of schools in achieving educational goals, to help teachers to be more aware and understand the needs and problems faced by students. The function of educational supervision consists of various activities that must be done, but in essence the activities include four things: (1) carrying out educational leadership, (2) conducting research, (3) conducting objective assessment, and (4) carry out appropriate services.